Oxidative Stress in the Rostral Ventrolateral Medulla Contributes To Cardiovascular Regulation in Preeclampsia - Yan, Jiu-Qiong; Huang, Fang; Hao, Fan; Su, Xiao-Ling; Meng, Qi; Xu, Ming-Juan (Frontiers in Physiology, 2017)
Background: It has been demonstrated that preeclampsia, a pregnancy-specific hypertension disorder, is characterized by high blood pressure (BP) and sympathetic overactivity. Increased reactive oxygen species (ROS) in the rostral ventrolateral medulla (RVLM), a key region for controlling sympathetic tone, has been reported to contribute to high level of BP and sympathetic outflow. The aim of the present study was to determine the role of the RVLM ROS in mediating the preeclampsia-associated cardiovascular dysfunction. Methods: The animal model of preeclampsia was produced by administration of desoxycorticosterone acetate (DOCA) to pregnant rats. Results: Compared with normal pregnant rats without DOCA treatment (NP), the protein concentration and norepinephrine excretion in 24-hour urine, as well as BP in pregnant rats with DOCA treatment (PDS) were significantly increased. The levels of superoxide anion and the protein expression of NADPH oxidase subtype (NOX4) in the RVLM were significantly increased in PDS than in NP groups. Furthermore, microinjection of the superoxide dismutase (SOD) mimic Tempol (5 nmol) into the RVLM significantly decreased BP, heart rate, and renal sympathetic never activity in PDS but not in NP group. Conclusion: The present data suggest that high BP and sympathetic overactivity in preeclampsia rats is associated with increased oxidative stress in the RVLM via upregulation of NOX4 expression.